Genetic screening test for psoriatic arthritis and UVB irradiation potential responders: A new tool to identify psoriasis subpopulation patients? - Torello Lotti; Linda Tognetti; Massimiliano Galeone; Nicola Bruscino; Silvia Moretti; Simonetta Giorgini (Wolters Kluwer Medknow Publications, 2011)
Psoriatic arthritis (PsA) is a psoriasis-associated inflammatory disease of the joints and enthuses. The occurrence of PsA is linked to the complex interplay of gene environment, and immune system. Genetic factors have long been recognized to play an important role in PsA. Genes within the major histocompatibility complex (MHC) region have been shown to be associated with PsA. These include genes coded in the HLA region, (especially Class I antigens) and non-HLA genes (i.e., MHC class I chain-related antigen A, MICA, and TNF-α genes). Association studies in PsA have also identified a number of genes outside MHC region, including interleukin-1 (IL-1) gene cluster, killer-cell immunoglobulin-like receptors (KIRs), and IL-23R genes. Established systemic treatments for moderate-severe psoriasis and PsA may be potentially dangerous and usually time consuming for the patient and often expensive for the National Health Systems. Tests which could predict which subset of psoriatic patients could develop the most severe forms of the disease (i.e., PsA) or will respond to well-established (UVB irradiation) or other systemic treatments are now required. The goal of genetic test screening is to rapidly and safely identify subjects for preventive or early treatment or extended surveillance prior to the onset of signs and symptoms. Genetic tests today represent a reliable investigation procedure which could rapidly and consistently improve the diagnostic ability of the dermatologist and contribute to the early and correct treatment of the different subsets of PsA.